PERSEPSI MASYARAKAT DI RW.4 KELURAHAN KUJANGSARI KECAMATAN BANDUNG KIDUL TERHADAP PROFESI APOTEKER DALAM CEGAH STUNTING - Kusumahati, Eva; gestina, Auliya; Nursanti, Amelia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Indonesia is one of the countries that has a fairly high prevalence of stunting. Provision of suplement ASI Booster maternal health and prevent child stunting requires clear information from a pharmacist as a care giver. This study aims to determine the perception of the public on the role of pharmacists and to know the perception of society to the pharmacist's profession as a source of drug information. The method of this research is descriptive observational with quetioner. The results of the study in the form of continuum review are all respondents' answers are in the area agree with the implementation of the score of 79.09% and most respondents have given the answer strongly agree (32.85%) and agree (61.43%) if the pharmacist acts as a source drug information, so that respondents have known and agreed that all aspects of the drug are the roles and responsibilities of a pharmacist.